Habitação Mínima: projecto, produção e mercado - Sara Patrícia Reis Vila Cova (2016)
A refletion about the minimum needs that a house has to satisfy to be considered appropriate, imediatly raises the question of: what is this physical, functional and psychological minimum where is possible to dwell with dignity? around which we realize all of that investigation work. The goal is to reflect about the concept of minimum dwelling in the context of current housing, through the investigation of concret cases of controlled housing costs and real estate market. So, beyond the study of theoretical and laboratory speculations, we favor the mecanisms of promotion and market that haven´t been noticeably investigated in the sphere of architecture, and seem restricted to construction and economic siences. The methodology is the review of the multiple and diverse dimentions of minimum dwelling: the process of promotion, where we inquire about the role of the Instituto da Habitação e Reabilitação Urbana; the architectural project, that implies the satisfaction not only of physical needs but also psychological and spiritual needs; the real estate market, responsible for the sale, purchase or rental of housing as property or product; the updated notion of family, essential unity that appropriates and expresses in space; and the ways of dwell in constant social and cultural evolution. This work intends to put in the contemporary debate the issue of minimum dwelling, in the scope of cost and resources reduction and without compromising quality, in order to satisfy the universal right to housing and facing it, above all, as a stimulant challenge of the imagination in Architecture.